2010
DOI: 10.1002/acr.20169
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported knee and foot alignments in early adult life and risk of osteoarthritis

Abstract: Objective. To determine whether self-reported early adult life malalignment of knees or feet are risk factors for knee or hip osteoarthritis (OA). Methods. Participants in the Genetics of Osteoarthritis and Lifestyle case-control database were sent a questionnaire (n ‫؍‬ 3,022) containing line-drawing instruments for self-reported knee and foot alignment at ages 20 -29 years. Respondents were categorized as having straight, valgus, or varus knee, and straight, toe-in, or toe-out feet. Radiographic criteria wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 39 publications
3
42
1
Order By: Relevance
“…A case–control study of 1901 patients found early-life knee malalignment (especially varus) was associated with the later development of knee OA 39. The same self-reported instrument was also used in a cohort study of 2156 healthy controls and found that early-life self-reported knee varus or valgus malalignment was also a cause of knee pain 8.…”
Section: Discussionmentioning
confidence: 99%
“…A case–control study of 1901 patients found early-life knee malalignment (especially varus) was associated with the later development of knee OA 39. The same self-reported instrument was also used in a cohort study of 2156 healthy controls and found that early-life self-reported knee varus or valgus malalignment was also a cause of knee pain 8.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of prevention, they may be classified into non-modifiable (eg, age, gender, genetic susceptibility/family history) and potentially modifiable risk factors (eg, body mass index (BMI), occupational risk, joint injury, quadriceps weakness, nutrients, bone mineral density and oestrogen deficiency) 9. Some new risk factors have been recently identified such as the longer ring finger (2D:4D ratio),11 12 varus/valgus mal-alignment13 14 and genetic predisposition15 16 but many of these have yet to be ratified.…”
mentioning
confidence: 99%
“…Thus, separating data for the knee and the hip joint could potentially be important. Similarly, self-reported presence of varus knee, valgus knee, and toe-in/out angles during early adult life has been reported to be associated with increased risk of knee but not hip OA [8]. We reported the prevalence of malalignment separately for the population with prolonged knee pain and the population with prolonged hip pain.…”
Section: Discussionmentioning
confidence: 93%
“…Important risk factors for knee and hip OA include age, obesity, and female gender [2][3][4], but recent studies also suggest that physical inactivity may play a role [5]. In addition, biomechanical factors such as malalignment and occupational physical exposure are considered to modify the risk of OA development by altering joint loading [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation